Teknologi Pemanenan Aliran Permukaan (Run Off) Pada Pertanian Lahan Kering - Bafdal, Nupilihan (Universitas Medan Area, 2020)
The area of dry land in Indonesia is quite high, reaching 148 million hectares spread across each of the Indonesian archipelago. Usually farmers plant dry land with rice, palawidja or other annual crops such as coconut, cassava and tree crops. Dry land has constraints, namely limited water for plants, especially in the dry season, because it only relies on water from mere rain sources; that is why land productivity is not optimal which in turn will have an impact on crop yields. The purpose of this study is to examine the harvesting run off in dry land, and can be managed as a source of irrigation water, so that productivity and carrying capacity of land can be increased. The research method uses descriptive analytic survey method that observes field conditions, mapping field locations and analysis of potential run-off. The results showed that the pool harvesting surface runoff during the rainy season was 43 m3. Dry land can increase IP of 2 by planting patterns, namely sweet corn -sweet corn -sweet potato. Water balance analysis shows that the water deficit period occurred in May to September. Surface harvesting technology as a source of irrigation water can meet water needs in the dry season.